The Drama of International Relations: A South China Sea Simulation1. Issue 4 (5th August 2013) - Kempston, Tanya; Thomas, Nicholas
Abstract : A fundamental challenge in teaching international relations is the need to bridge the students' learning gap between knowledge and practice, providing them with opportunities to reflect on what they have learned and allowing them to develop a greater cognition of their own abilities in the area. The South China Sea is one of the most long‐running and complex disputes in contemporary international affairs. It remains one of the few flashpoints around the globe that holds the potential to directly escalate into a great‐power conflict. Understanding this issue is therefore an important task for students of IR and strategic studies, but the complexity of the dispute makes teaching it in a regular seminar/lecture format problematic. This article describes a simulation run in a masters‐level class in the spring 2012 semester designed to address this pedagogical challenge. It started with a jeopardized security operation on a disputed oil platform in a real‐world territory claimed by multiple states. This article explores the theoretical conception of the simulation, its structure and design, the post‐simulation debriefing as well as considerations as to how the simulation might be modified to be more engaging to students and more relevant to intended learning outcomes.